Dari "Wealth of Nations" Menuju "Wealth of Corporations"; Kajian MP3EI Dalam Perspektif Hak Asasi Manusia - Buhaerah, Pihri; Puspitasari, Arum; Nurjaman, Rusman (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2014)
For a long time, development is solely measured by the rate of economic growth. Measuring the success of development by simply referring to economic growth contains many ï¬‚aws because it ignores the fairness of income distribution which resulted in a large gap between the rich and the poor. Various adverseeï¬ects of growth-orienteddevelopmenthave prompted the emergence ofnew thinking to rectify the deï¬nition of development. The new thinking led to the expansion ofa deï¬nition of human-centered development, as deï¬ned in the oonoept of human rights-based development. In the perspective of human rights, development deï¬ned as "human-centered, participatory, and special attention to the vulnerable groups and environmentâ€œ. Economicgrowth is still needed, but the development process should also ensure equitable distribution, enhancement of human capabilities, and intended to expand the human choices. Currently, the eï¬‚brts to promote a human rights approach in development process are no more than just new concepts on paper rather than implementation. Therefore, there must be a joint eï¬‚brt and commitment to fundamentally change the development paradigm. This MPSEI study in human rights perspective is an qï¬rt to ask jbr a commihnent from state oï¬‚icials to integrate human rights-based approach to Indonesia development. This ejjbrt shall be done continuesly to promote human rightsas a main development perspective, as well as theend and the means ofdevelopment.